VALIDATION OF THE SERBIAN ADAPTATION OF THE EMOTION REGULATION QUESTIONNAIRE (ERQ) - Popov, Stanislava; Janičić, Bojan; Dinić, Bojana (Primenjena psihologija, 2016)
The aim of this study is to examine validity of a Serbian adaptation of the Emotional Regulation Questionnaire (ERQ: Gross & John, 2003). ERQ was based on Gross’ Process Model of Emotion Regulation, according to which emotion regulation can occur before and after the occurrence of emotional response. The questionnaire measures two strategies of emotional regulation: Cognitive Reappraisal (CR), which occurs before emotional response is fully generated and refers to reinterpretation of emotionally evoking situation, and Emotion Suppression (ES), which refers to regulation of already formed emotional response. In Study 1, carried out on 623 participants from the general population (35.5% male, mean age 27.97), a factor structure of the ERQ was examined. The results of a confirmatory factor analysis indicated that the best model assumes two factors – ES and CR, while CR had a bifactor structure. A part of the CR variance could be attributed to the method effect mainly derived from the items related to reappraisal of positive emotions. In Study 2, carried out on a sample of 223 students (30.5% male), divergent validity of the ERQ was examined in respect to correlation with the HEXACO dimensions of personality and the dimensions of affect. The correlations with the ERQ raw scores as well as the scores with the method effect partialled out were examined. Although the correlations with the partialized scores were slightly higher, generally, they were not different from the correlations with the raw scores. In other words, the method effect was practically negligible. ES was negatively related to Emotionality, Extraversion, and Positive Affect. CR was positively related to Extraversion and Positive Affect, and negatively to Negative Affect, confirming validity of the ERQ.